التحليل المكاني لتركيب الأحدب وأثره الجيومورفولوجي في تغير مجرى نهر دجلة بين النعمانية والكوت - خليف, حسين عذاب; عبد الحسين, أحمد هاشم; ألساعدي, حسين كريم حمد (lark, 2019)
AbstractAnalysis Spatial of AL- Ahdab Structure and Effect's Geomorphology in Changing the Channel of Tigris River between Numaniyah and Kut.        The study based on the satellite images for three years (1984-1998-2015) to extract water bodies of Tigris river by using AWEI to detect the impact of Ahdab anticline structure on geomorphologic features. The subsurface anticline structures have a big role in changing channel and bank erosion of the rivers because of the uplifting movements of those structures. The uplifting movements change base-level of the rivers and block water in certain points along river’s channel. These changings will lead to change the erosion system inside the river’s channel in order to find lands with less elevation.        The structure of Ahdab is located in the south of Kut city. Ahdab effects on the channel of Tigris River by the appearance of meanders, twists, ox-bow lake, and river’s islands. The structure changes the river bank erosion to be more frequent and concentrated on the right bank rather than left bank because Ahdab is located on the left side. It means the Tigris River is now moving toward northern east, where the main road of (Kut-Baghdad) is located. This problem requires urgent solutions such as paving the bank of river by limestone, strength the natural levees by adding soil and compacting, and monitoring the base level to avoid any change by uplifting movement.       These structures are often as oil reservoir as in the case study Ahdab oil structure in Wassit Governorate. It is considered one of the most important oil reservoirs because it contains (1) billion barrels as oil reserve and this amount may be increased by more future investigations.      The oil recovery of Ahdab field started in 2011 with capacity of oil recovery reached up to (60000) barrels/day, and after six months capacity jumped up to (120000) barrels/day, and nowadays the product is (140000) barrel/day. Ahdab oil field is operated by the (Chinese National Company for Oil). Oil recovery operations now are from (177) wells out of (404) oil wells, which is planned to be dug it in future.      Ahdab field supplies fuel (67000 barrel/daily) to Zubeidia power station that belongs to Azizia city at the north of the study area. It also supplies gas to gas filling plant for local use in Wassit area and neighbors’ areas.